In a time of distance : & other poems - McCall Smith, Alexander, 1948- (Polygon, 2020)
In a Time of Distance, the poem from which the collection take its title, was written at the start of the global pandemic which struck at the start of 2020, here the author reminds us of what is important in life and to focus on love, friendship and family. And it is this approach to life that makes this collection a captivating celebration of love and friendship, of Scotland and people, of animals and books. Looking at the World through the lens of this writer, it is a better, more humane place. Throughout the collection there are moments of swoop and soar, descriptions that will make you laugh and realign your view. The author reminds us to look at the World differently, to stop once in while and look up at the sky.